Maharam traces on von Neumann algebras - Zakirov, B. S.; Chilin, V. I. (Methods of Functional Analysis and Topology, 2010)
Traces Φ on von Neumann algebras with values in complex order complete vector lattices are considered. The full description of these traces is given for the case when Φ is the Maharam trace. The version of Radon-Nikodym-type theorem for Maharam traces is established.